AB0775 The Diagnostic Value of the Asas Recommendations for Early Referral of Axial Spondyloarthritis in Primary Care Patients with Chronic Low Back Pain. (9th June 2015) - Van Hoeven, L.; Vergouwe, Y.; de Buck, P.; Han, K.; Luime, J.; Hazes, J.; Weel, A.
Abstract : Background: There is a delay between the onset of the first back pain symptoms and the final diagnosis of axial spondyloarthritis (axSpA). This delay can be explained by difficulties for primary care physicians to recognize and subsequently refer potential axSpA patients in the huge number of chronic low back pain (CLBP) patients seen in primary care. At this moment there is no widely accepted referral strategy. Recently the ASAS workgroup proposed recommendations for early referral although these were not yet validated in a primary care setting. Objectives: To test the ASAS proposed recommendations for early referral in a primary care setting. Methods: Our study population included primary care patients (18-45 years) with CLBP (≥3 months, age at back pain onset <45 years) from two Dutch cross-sectional studies. No specific axSpA features were used to include patients. Patients already diagnosed with ankylosing spondylitis were not invited. Patients underwent a diagnostic work-up, including a standardized history, physical examination, HLA-B27 and CRP. A conventional radiograph and MRI of the sacroiliac joints was obtained. Definite axSpA was defined by the ASAS criteria. The ASAS recommendations are applicable in patients with CLBP (≥3 months) and back pain onset before 45 years and should be referred if at least one of the following parameters is present: inflammatory back pain, HLA-B27 positivity, sacroillitis on imaging (X-ray or MRI), peripheral manifestations (arthritis, enthesitis, dactylitis), extra-articulair manifestations (psoriasis, inflammatory bowel disease, uveitis), positive family history for SpA, good response to non-steroidal anti-inflammatory drugs (NSAIDs), elevated acute phase reactants. To test these recommendations, sensitivity, specificity and positive predictive value were calculated. Results: In total 941 primary care CLBP patients participated (58% female, mean age 36.0 years), of those were 181 (19%) identified as axSpA, 54 of the 181 (30%) were newly diagnosed with ankylosing spondylitis. 773 (82%) patients had at least one parameter present and thus according to the recommendations should be referred to the rheumatologists. The sensitivity of the ASAS recommendation is 100% (181/181), the specificity 22% (168/760) and the positive predictive value 23% (181/773) (Table 1 ). Conclusions: The ASAS recommendation for early referral has a perfect sensitivity in primary care CLBP population. However this comes at the cost of a low specificity, meaning that almost 80% of the referred patients will undergo unnecessary diagnostic work up. A more specific referral strategy will be needed in daily primary care. Acknowledgements: An unrestricted research grant was provided by AbbVie. Disclosure of Interest: None declared